Secondary battery, negative current collector, method for manufacturing the same, and electric device
Patent Information
- Application Number
- CN202510420864.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-03
- Publication Date
- 2026-10-16
AI Technical Summary
在传统的二次电池中,常用的负极集流体较难实现质轻和延展性的兼顾,不利于其在航天航空等要求电芯轻量化领域的应用
[0031] The fourth aspect of this application provides an electrical device including the secondary battery described in the first aspect of this application.
Smart Images

Figure CN122930992A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of battery technology, and in particular to a secondary battery, a negative electrode current collector, a method for preparing the same, and an electrical device thereof. Background Technology
[0002] In recent years, with the increasingly widespread application of secondary batteries, represented by lithium-ion batteries, they have been widely used in energy storage power systems such as hydropower, thermal power, wind power, and solar power plants, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace, and many other fields. In traditional secondary batteries, it is difficult to achieve a balance between lightweight and ductility in the commonly used negative electrode current collector, which is not conducive to their application in aerospace and other fields that require lightweight cells. Summary of the Invention
[0003] This application provides a secondary battery, a negative electrode current collector, a method for preparing the same, and an electrical device thereof. The negative electrode current collector can effectively balance light weight and ductility, which is beneficial for its application in aerospace and other fields that require lightweight battery cells.
[0004] To achieve the above objectives, a first aspect of this application provides a secondary battery including a negative electrode sheet, the negative electrode sheet including a negative current collector, the negative current collector including a substrate layer and a metal layer disposed on at least one side of the substrate layer, wherein the substrate layer is made of aluminum and / or magnesium, and the metal layer contains metal grains.
[0005] In the secondary battery provided in this application, the negative electrode current collector uses aluminum and / or magnesium as the substrate layer, and a metal layer is disposed on the substrate layer. Using aluminum and / or magnesium as the substrate layer helps reduce the weight of the negative electrode current collector. The metal layer disposed on the substrate layer effectively reduces the intercalation of active ions by aluminum and / or magnesium in the substrate layer, increasing the battery capacity. Furthermore, the presence of metal grains in the metal layer indicates that the metal layer is in a crystalline form. A crystalline metal layer has good toughness and ductility, making it less prone to breakage during winding, which is beneficial for the preparation of the negative electrode current collector and its normal operation in the battery cell. Therefore, this negative electrode current collector achieves a good balance between light weight and ductility.
[0006] In some embodiments of this application, the average grain size of the metal grains is 10nm~100nm, and can be selected as 10nm~50nm.
[0007] In some embodiments of this application, one or more of the following conditions are met:
[0008] (1) The porosity of the metal layer is less than or equal to 2 cells / dm 2 ;
[0009] (2) The single-layer elongation of the metal layer is greater than or equal to 1%, and can be selected as 1% to 5%;
[0010] (3) The metal layer comprises one or more materials selected from nickel and nickel alloys, chromium and chromium alloys;
[0011] Optionally, the nickel alloy includes one or more of nickel-iron alloy, nickel-copper alloy, and nickel-chromium alloy;
[0012] Optionally, the chromium alloy includes one or more of chromium-nickel alloy, ferrochrome alloy, and ferrochrome-nickel alloy;
[0013] (4) The thickness of the metal layer is 0.5μm~2μm, and can be selected as 0.5μm~1.5μm.
[0014] In some embodiments of this application, the negative electrode current collector further includes a transition layer disposed between the substrate layer and the metal layer, the transition layer comprising zinc;
[0015] Optionally, the thickness of the transition layer is 10nm~300nm, and optionally 20nm~100nm.
[0016] In some embodiments of this application, the negative electrode current collector further includes an antioxidant layer, which is disposed on the surface of the metal layer on the side away from the transition layer;
[0017] Optionally, the thickness of the antioxidant layer is 1nm~200nm, and can be 20nm~100nm;
[0018] Optionally, the antioxidant layer comprises chromium-containing oxides and / or nickel-containing oxides.
[0019] A second aspect of this application provides a negative electrode current collector comprising a substrate layer and a metal layer disposed on at least one side of the substrate layer, wherein the substrate layer is made of aluminum and / or magnesium, and the metal layer comprises metal grains.
[0020] In some embodiments of this application, it is the negative electrode current collector in the secondary battery described in the first aspect of this application.
[0021] A third aspect of this application provides a method for preparing a negative electrode current collector, comprising:
[0022] A metal layer is prepared on at least one side of a substrate layer by an electroplating process, wherein the substrate layer is made of aluminum and / or magnesium, and the metal layer comprises metal grains.
[0023] This application proposes the aforementioned preparation method, in which electroplating replaces conventional chemical plating and physical processes to prepare a metal layer on a foil of lightweight metals such as aluminum. The metal layer prepared by electroplating is phosphorus-free and can form finer metal grains, resulting in lower brittleness and hardness, and better toughness. This overcomes the problems associated with chemical plating, facilitating its application in batteries. Furthermore, compared to physical processes such as magnetron sputtering, electroplating is relatively simpler, requires less sophisticated equipment, reduces process costs, and is suitable for large-scale industrialization.
[0024] In some embodiments of this application, before preparing the metal layer, a zinc-containing transition layer is prepared on at least one side of the substrate layer by a chemical zinc immersion process.
[0025] Optionally, the zinc immersion solution in the chemical zinc immersion process comprises zinc oxide, sodium hydroxide, potassium sodium tartrate, ferric chloride, and sodium nitrate.
[0026] Further optionally, in the zinc immersion solution, the concentration of zinc oxide is 20 g / L to 30 g / L, the concentration of sodium hydroxide is 110 g / L to 130 g / L, the concentration of potassium sodium tartrate is 45 g / L to 55 g / L, the concentration of ferric chloride is 1 g / L to 2 g / L, and the concentration of sodium nitrate is 1 g / L to 2 g / L;
[0027] Optionally, the chemical zinc immersion process includes a first zinc immersion treatment, a zinc stripping treatment, and a second zinc immersion treatment;
[0028] Further optionally, the first zinc immersion treatment takes 30s to 60s;
[0029] Further optionally, the zinc stripping process takes 30s to 60s;
[0030] Further optionally, the second zinc immersion treatment takes 10s to 20s.
[0031] The fourth aspect of this application provides an electrical device including the secondary battery described in the first aspect of this application.
[0032] The electrical device of this application includes the secondary battery provided in this application, and therefore has at least the same advantages as the secondary battery.
[0033] Details of one or more embodiments of this application are set forth in the following drawings and description. Other features, objects, and advantages of this application will become apparent from the specification, drawings, and claims. Attached Figure Description
[0034] To better describe and illustrate the embodiments or examples provided in this application, reference may be made to one or more accompanying drawings. Additional details or examples used to describe the drawings should not be considered as limiting the scope of any of the disclosed applications, the currently described embodiments or examples, or the best mode of conduct of these applications as currently understood. Furthermore, the same reference numerals denote the same parts throughout the drawings. In the drawings:
[0035] Figure 1 This is a schematic diagram of the negative electrode current collector according to one embodiment of this application.
[0036] Figure 2 This is a schematic diagram of a battery cell according to one embodiment of this application.
[0037] Figure 3 for Figure 2 An exploded view of a battery cell according to one embodiment of this application is shown.
[0038] Figure 4 This is a schematic diagram of a battery device according to one embodiment of this application.
[0039] Figure 5 This is a schematic diagram of a battery pack according to one embodiment of this application.
[0040] Figure 6 for Figure 5 An exploded view of a battery pack according to one embodiment of this application is shown.
[0041] Figure 7 This is a schematic diagram of an electrical device that uses a secondary battery as a power source according to one embodiment of this application.
[0042] Explanation of reference numerals in the attached figures:
[0043] 1 Battery pack; 2 Upper casing; 3 Lower casing; 4 Battery assembly; 5 Battery cell; 51 Housing; 52 Electrode assembly; 53 Cover plate; 6 Electrical device; 10 Base layer; 11 Transition layer; 12 Metal layer; 13 Anti-oxidation layer. Detailed Implementation
[0044] Hereinafter, some embodiments of this application are described in detail with appropriate reference to the accompanying drawings. However, some unnecessary details may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of actually identical structures may be omitted. This is to avoid making the following description unnecessarily lengthy and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided to enable those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.
[0045] The "range" disclosed in this application can be defined in the form of a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints; any endpoint can be independently included or excluded, and they can be combined arbitrarily, meaning any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values 1 and 2 are listed, and maximum range values 3, 4, and 5 are also listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0" and "5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when describing a parameter as an integer ≥ 2, it is equivalent to listing integers such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, and 12 for that parameter. For instance, when describing a parameter as an integer selected from "2-10", it is equivalent to listing the integers 2, 3, 4, 5, 6, 7, 8, 9, and 10.
[0046] In this application, the terms "multiple" or "various" are used unless otherwise specified, referring to a quantity greater than or equal to 2. For example, "one or more" means one or more types.
[0047] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.
[0048] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment or implementation of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments. The term "implementation" as used herein has a similar understanding.
[0049] Those skilled in the art will understand that the order in which the steps are written in the methods of various embodiments or examples does not imply a strict execution order and does not constitute any limitation on the implementation process. The detailed execution order of each step should be determined by its function and possible internal logic. Unless otherwise specified, all steps of this application may be performed sequentially or randomly, preferably sequentially. For example, if the method includes steps (a) and (b), it means that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, if the method may also include step (c), it means that step (c) can be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0050] In this application, "optionally," "optionally," and "optional" mean that something is optional, that is, it means that it is selected from either "with" or "without." If there are multiple "optional" entries in a technical solution, unless otherwise specified and there are no contradictions or mutual constraints, each "optional" entry shall be independent.
[0051] Currently, copper foil is commonly used as the negative electrode current collector in traditional lithium-ion batteries. However, copper foil has a high density and is heavy for the same thickness, which will take up more weight of the battery cell. This is not conducive to improving the weight energy density of the battery cell, nor is it conducive to its application in aerospace and other fields that require lightweight battery cells.
[0052] To address the aforementioned technical challenges, there are precedents of using lightweight aluminum foil to replace copper foil, and then fabricating other metal layers (such as nickel layers) on the aluminum foil through chemical plating or physical processes (such as magnetron sputtering and vapor deposition) to serve as negative electrode current collectors. However, metal layers (such as nickel layers) prepared by chemical plating typically contain phosphorus, making it difficult for the metal layer to form a crystalline structure and more likely to form amorphous alloys (such as nickel-phosphorus alloys). These amorphous alloys result in metal layers with high brittleness and hardness, making them prone to breakage during winding and unsuitable for use as current collectors in batteries. While metal layers prepared through physical processes are suitable for battery applications, the fabrication processes, such as magnetron sputtering, are generally complex, require sophisticated equipment, and are costly, hindering industrialization.
[0053] In view of this, this application provides a secondary battery in which aluminum and / or magnesium are used as the base layer in the negative electrode current collector, and a crystalline metal layer is disposed on the base layer. This not only enables the negative electrode current collector to have better toughness and ductility, allowing it to work normally in the battery cell, but also significantly reduces the weight compared to copper foil of the same thickness. This facilitates the improvement of the weight energy density of the battery cell and is beneficial for its application in aerospace and other fields that require lightweight battery cells.
[0054] In one aspect, this application provides a secondary battery comprising a negative electrode sheet, wherein the negative electrode sheet includes a negative current collector. (See also...) Figure 1 The negative electrode current collector includes a substrate layer 10 and a metal layer 12 disposed on at least one side of the substrate layer 10, wherein the material of the substrate layer 10 includes aluminum and / or magnesium, and the metal layer 12 contains metal grains.
[0055] In the secondary battery provided in this application, the negative electrode current collector uses aluminum and / or magnesium as the substrate layer 10, and a metal layer 12 is disposed on the substrate layer. Using aluminum and / or magnesium as the substrate layer 10 helps reduce the weight of the negative electrode current collector. The metal layer 12 disposed on the substrate layer effectively reduces the intercalation of active ions by aluminum and / or magnesium in the substrate layer 10, increasing the battery capacity. Simultaneously, the presence of metal grains in the metal layer 12 indicates that the metal layer is in a crystalline form. A crystalline metal layer has good toughness and ductility, making it less prone to breakage during winding, which is beneficial for the preparation of the negative electrode current collector and its normal operation in the battery cell. Therefore, this negative electrode current collector achieves a good balance between light weight and ductility.
[0056] As an example, the method for determining whether a metal layer contains metal grains is as follows: Place the metal layer separated from the negative electrode current collector under a scanning electron microscope (SEM, such as Sigma30), scan any area at a magnification of 3000x, and observe whether grains and grain boundaries are present.
[0057] In some embodiments, the metal layer 12 comprises one or more materials selected from nickel and nickel alloys, chromium and chromium alloys; in some embodiments, the nickel alloy comprises one or more selected from nickel-iron alloys, nickel-copper alloys, and nickel-chromium alloys; in other embodiments, the chromium alloy comprises one or more selected from chromium-nickel alloys, chromium-iron alloys, and chromium-nickel-iron alloys.
[0058] Nickel and nickel alloys, or chromium and chromium alloys, possess high chemical stability. In the battery's operating environment, they are unlikely to react chemically with substances such as electrolytes, and the resulting surface film also exhibits stability, effectively preventing the intercalation of active ions and enabling the battery to achieve high capacity. Furthermore, the electronegativity of nickel and nickel alloys, or chromium and chromium alloys, allows for the preparation of metal layers through electroplating.
[0059] In some embodiments, the average grain size of the metal grains is 10 nm to 100 nm, optionally 10 nm to 50 nm, and further optionally 12 nm to 18 nm. For example, the average grain size of the metal grains can be 10 nm, 13 nm, 15 nm, 17 nm, 21 nm, 23 nm, 26 nm, 29 nm, 30 nm, 39 nm, 48 nm, 57 nm, 66 nm, 75 nm, 84 nm, 93 nm, 100 nm, or within any range of the above values. When the grain size of the metal grains is within the above range, the metal layer is essentially free of pinholes and pores, and is relatively uniform and dense, while also exhibiting high brightness. This effectively blocks the penetration of active ions and provides good corrosion resistance; simultaneously, it reduces the brittleness and hardness of the metal layer, giving it higher toughness and elongation.
[0060] As an example, the grain size of the grains in the metal layer can be tested by the following method: place the metal layer separated from the negative electrode current collector under a scanning electron microscope (SEM, such as Sigma30), scan any area (such as 1μm×1μm) at a magnification of 3000x, measure the maximum radius of all grains in the area, and obtain the average grain size of the fine grains by averaging.
[0061] In some embodiments, the porosity of the metal layer is less than or equal to 2 cells / dm. 2 Thus, the metal layer has high density, which can effectively block the penetration of active ions and has good corrosion resistance.
[0062] It should be noted that the "porosity of the metal layer" mentioned in this application refers to the number of pores or pinholes contained on the surface of a unit area (i.e., 1dm × 1dm) of the metal layer.
[0063] As an example, the porosity of the metal layer can be tested using the following method: the porosity is measured using a metallographic microscope with a magnification of 10x. The stripped metal layer is placed on a light-emitting screen, and the holes that allow light to pass through are observed. The number of holes per unit area (i.e., 1dm × 1dm) is then calculated.
[0064] In some embodiments, the single-layer elongation of the metal layer is greater than or equal to 1%, optionally ranging from 1% to 5%. This results in lower brittleness and hardness, better flexibility, and ease of winding into the desired shape during battery fabrication, making it suitable for battery applications.
[0065] It should be noted that the "single-layer elongation of the metal layer" mentioned in this application refers to the elongation of a metal layer with a thickness of less than or equal to 2 μm.
[0066] As an example, the elongation of a single metal layer can be tested using the following method: Specific testing methods can be found in GB / T5230-1995 "Electrolytic Copper Foil" standard. A sample is cut from the metal layer and prepared into a standard tensile specimen for testing.
[0067] In some embodiments, the thickness of the metal layer 12 is 0.5 μm to 2 μm, and can be selected as 0.5 μm to 1.5 μm. For example, the thickness of the metal layer 12 can be 0.5 μm, 0.7 μm, 1 μm, 1.3 μm, 1.5 μm, 1.7 μm, 2 μm, or within any range of the above values. This configuration not only allows the metal layer 12 to effectively prevent the intercalation of active ions, but also allows the negative electrode current collector to have the lightest possible weight.
[0068] In some embodiments, the negative electrode current collector further includes a transition layer 11 disposed between the substrate layer 10 and the metal layer 12, the transition layer 11 comprising zinc.
[0069] If the metal layer is directly placed on the substrate layer, an oxide layer (such as an aluminum oxide layer) easily forms on the surface of the substrate layer, resulting in insufficient bonding between the metal layer and the substrate layer. Consequently, the metal layer is prone to detachment during battery operation. Therefore, introducing a transition layer between the substrate layer and the metal layer helps improve the bonding strength between them. Furthermore, the zinc contained in the transition layer 11, compared to other metal materials, has a relatively high alloying ability. When used as a transition layer, it more easily forms an alloy transition layer with adjacent metals or alloys, thus further enhancing the bonding strength. Simultaneously, due to its relatively low electrode potential, it is more readily corroded in the electrolyte environment, further contributing to the maintenance and improvement of the bonding strength.
[0070] Furthermore, as the battery operating time increases, when the metal layer 12 weakens its ability to block the insertion of active ions, the zinc-containing transition layer 11 can also act as a further barrier layer to block the insertion of active ions into the substrate layer. Thus, through the double barrier layer composed of the metal layer and the transition layer, the insertion of active ions into the substrate layer can be effectively weakened or prevented, thereby effectively improving the battery capacity.
[0071] It should be noted that the ions in the "metal layer" mentioned in this application refer to active ions, that is, ions that can migrate between the positive and negative electrodes of the battery and participate in the charging and discharging chemical reactions of the battery, thereby realizing the interconversion of electrical energy and chemical energy, including lithium ions.
[0072] As an example, the presence of a zinc layer in the negative electrode current collector can be tested using the following method:
[0073] The cross-section of the negative electrode current collector was tested using SEM (scanning electron microscope) and EDS (energy dispersive X-ray spectrometer). Surface scanning (EDS) was performed to test the elemental content. When the zinc content was ≥1%, it indicated that a zinc layer existed in the negative electrode current collector. At the same time, the layering of the negative electrode current collector was observed (SEM) to determine the overall structural design of the negative electrode current collector.
[0074] In some embodiments, the thickness of the transition layer 11 is 10 nm to 300 nm, and can be selected as 50 nm to 200 nm. For example, the thickness of the transition layer 11 can be 10 nm, 50 nm, 70 nm, 100 nm, 120 nm, 140 nm, 160 nm, 180 nm, 200 nm, 230 nm, 260 nm, 300 nm, or within any range of the above values. This configuration allows for a high bonding force between the substrate layer 10 and the metal layer 12, while also enabling the negative electrode current collector to have a lighter weight.
[0075] In some embodiments, the thickness of the substrate layer 10 is 4 μm to 6 μm. For example, the thickness of the substrate layer 10 can be 4 μm, 4.3 μm, 4.7 μm, 5 μm, 5.3 μm, 5.7 μm, 6 μm, or within any range of the above values. This configuration allows the negative electrode current collector to have the lightest possible weight while still enabling it to function properly within the battery cell.
[0076] In some embodiments, the negative electrode current collector further includes an antioxidant layer 13, which is disposed on the surface of the metal layer 12 on the side away from the transition layer 11. This arrangement helps to improve the oxidation and corrosion resistance of the negative electrode current collector to substances such as electrolytes in the battery, while also filling pores to prevent the embedding of active ions.
[0077] In some embodiments, the thickness of the antioxidant layer 13 is 1 nm to 200 nm, and can be selected as 20 nm to 100 nm. For example, the thickness of the antioxidant layer 13 can be 1 nm, 5 nm, 10 nm, 30 nm, 50 nm, 70 nm, 100 nm, 120 nm, 140 nm, 160 nm, 180 nm, 200 nm, or within any range of the above values. This configuration allows the negative electrode current collector to have good antioxidant and corrosion resistance to substances such as electrolytes in the battery, while also minimizing the weight of the negative electrode current collector.
[0078] In some embodiments, the antioxidant layer comprises chromium-containing oxides and / or nickel-containing oxides. In some embodiments, the chromium-containing oxides include chromium trioxide and / or chromium oxide; the nickel-containing oxides include nickel oxide.
[0079] In the negative electrode current collector of this application, the thickness of each layer has a meaning known in the art and can be tested using methods known in the art. For example, the thickness of each layer can be measured by performing SEM testing on the cross-section of the negative electrode current collector.
[0080] Secondly, this application provides a negative electrode current collector; please refer to [link to relevant documentation]. Figure 1 The negative electrode current collector includes a substrate layer 10 and a metal layer 12 disposed on at least one side of the substrate layer 10, wherein the substrate layer 10 includes aluminum and / or magnesium, and the metal layer 12 contains metal grains.
[0081] In some embodiments, the negative electrode current collector is the negative electrode current collector in the secondary battery described in the first aspect of this application.
[0082] The negative electrode current collector provided in the second aspect of this application plays the same role in the secondary battery as that in the first aspect, and will not be described again here.
[0083] Thirdly, this application provides a method for preparing a negative electrode current collector, which can be used to prepare the negative electrode current collector of the first or second aspect of this application, and may include the following steps:
[0084] S1. A metal layer is prepared on at least one side of a substrate layer by an electroplating process, wherein the substrate layer is made of aluminum and / or magnesium, and the metal layer contains metal grains.
[0085] Currently, for aluminum-containing composite metal layers, other metal layers (such as nickel layers) are typically formed on aluminum foil using chemical plating or physical processes (such as magnetron sputtering and vapor deposition). However, metal layers prepared by chemical plating (such as nickel layers) inevitably contain phosphorus, making it difficult for the metal layer to form a crystalline morphology and more likely to form amorphous alloys (such as nickel-phosphorus alloys). These amorphous alloys result in metal layers with high brittleness and hardness, making them prone to breakage during winding and unsuitable for use as current collectors in batteries. While metal layers prepared by physical processes are suitable for battery applications, the preparation processes of physical processes such as magnetron sputtering are usually complex, require sophisticated equipment, and are costly, making industrialization difficult.
[0086] In view of this, this application proposes the aforementioned preparation method, in which electroplating replaces conventional chemical plating and physical processes to prepare a metal layer on a foil of lightweight metals such as aluminum. The metal layer prepared by electroplating is phosphorus-free and can form fine metal grains, resulting in lower brittleness and hardness, and better toughness. This overcomes the problems associated with the aforementioned chemical plating process, facilitating its application in batteries. Furthermore, compared to physical processes such as magnetron sputtering, electroplating is relatively simpler, requires less equipment, reduces process costs, is suitable for large-scale industrialization, and improves the ease of preparing negative electrode current collectors.
[0087] In some embodiments, the following steps may be included prior to preparing the metal layer:
[0088] S1'. A zinc-containing transition layer is prepared on at least one side of the substrate layer by a chemical zinc immersion process.
[0089] While electroplating overcomes the aforementioned drawbacks of chemical plating and physical plating processes, directly preparing a metal layer on lightweight metal foils such as aluminum via electroplating often results in a weak bond between the foil surface and the metal layer due to the formation of an oxide layer (such as an aluminum oxide layer), leading to easy detachment of the metal layer. Therefore, this application introduces the preparation of a transition layer before the metal layer. A zinc-containing transition layer is prepared between the substrate layer and the metal layer using a chemical zinc immersion process. This enhances the bond between the substrate layer and the metal layer, making the metal layer less prone to detachment and improving the structural stability of the negative electrode current collector. This chemical zinc immersion process is simple, low-cost, and also conducive to large-scale industrialization.
[0090] In some embodiments, the zinc immersion solution in the chemical zinc immersion process comprises zinc oxide, sodium hydroxide, potassium sodium tartrate, ferric chloride, and sodium nitrate.
[0091] In some embodiments, the zinc immersion solution contains zinc oxide at a concentration of 20 g / L to 30 g / L, sodium hydroxide at a concentration of 110 g / L to 130 g / L, potassium sodium tartrate at a concentration of 45 g / L to 55 g / L, ferric chloride at a concentration of 1 g / L to 2 g / L, and sodium nitrate at a concentration of 1 g / L to 2 g / L.
[0092] For example, in a zinc immersion solution, the concentration of zinc oxide can be 20 g / L, 21 g / L, 23 g / L, 25 g / L, 27 g / L, 29 g / L, 30 g / L, or within any range of these values; the concentration of sodium hydroxide can be 110 g / L, 113 g / L, 116 g / L, 119 g / L, 121 g / L, 123 g / L, 126 g / L, 129 g / L, 130 g / L, or within any range of these values; the concentration of potassium sodium tartrate can be 45 g / L, 46 g / L, 47 g / L, etc. The concentrations of ferric chloride can be 1 g / L, 1.2 g / L, 1.4 g / L, 1.6 g / L, 1.8 g / L, 2 g / L, or within any range of the above values; the concentrations of sodium nitrate can be 1 g / L, 1.2 g / L, 1.4 g / L, 1.6 g / L, 1.8 g / L, 2 g / L, or within any range of the above values.
[0093] The zinc immersion solution of this application contains all the above-mentioned components, and the components are matched with their corresponding concentrations. Compared with conventional electroplating zinc immersion solution formulations, the transition layer formed by the zinc immersion solution formulation specifically formulated in this application can achieve a tighter bond with the substrate layer and the metal layer, giving the negative electrode current collector excellent structural stability.
[0094] In some embodiments, the temperature of the chemical zinc immersion process is 20°C to 30°C. For example, this temperature can be 20°C, 25°C, 30°C, or any range thereof. The formulation of the aforementioned zinc immersion solution, combined with the temperature of this zinc immersion process, can enhance the adhesion between the prepared zinc-containing transition layer and the substrate layer and the metal layer, respectively.
[0095] In some embodiments, the chemical zinc immersion process includes a first zinc immersion treatment, a zinc stripping treatment, and a second zinc immersion treatment. In some embodiments, the first zinc immersion treatment lasts for 30 to 60 seconds; the zinc stripping treatment lasts for 30 to 60 seconds; and in other embodiments, the second zinc immersion treatment lasts for 10 to 20 seconds. For example, the first zinc immersion treatment time can be 30 seconds, 33 seconds, 39 seconds, 42 seconds, 48 seconds, 51 seconds, 56 seconds, 60 seconds, or any value within the range above; the second zinc immersion treatment time can be 10 seconds, 11 seconds, 13 seconds, 16 seconds, 19 seconds, 20 seconds, or any value within the range above. The aforementioned zinc immersion solution formulation, combined with the appropriate first and second zinc immersion treatment times, can enhance the adhesion between the prepared zinc-containing transition layer and the substrate layer and the metal layer, respectively.
[0096] In some embodiments, the electroplating process temperature is 45°C to 65°C; in other embodiments, the electroplating process current density is 5 to 30 A / dm³. 2 By adjusting parameters such as the temperature and / or current density of the electroplating process, as well as the formulation of the zinc immersion solution, the average grain size of the metal grains formed in the metal layer can be controlled, and it is beneficial to control the average grain size of the metal grains within a suitable range, so that the metal layer can obtain a high single-layer elongation.
[0097] In some embodiments, the above method may further include the following step: preparing an antioxidant layer 13 on the metal layer 12 by chemical passivation.
[0098] In some embodiments, before preparing the transition layer 11 by chemical plating, the following steps may be included: degreasing, alkaline etching and acid etching treatment of the substrate layer 10 to remove impurities and oxide film on the surface of the substrate layer.
[0099] In addition, the secondary battery and power-consuming device of this application will be described below with appropriate reference to the accompanying drawings.
[0100] Typically, a secondary battery consists of a positive electrode, a negative electrode, an electrolyte, and a separator. During charging and discharging, active ions move back and forth between the positive and negative electrodes, inserting and releasing. The electrolyte acts as a conductor between the positive and negative electrodes. The separator, positioned between the positive and negative electrodes, primarily prevents short circuits while allowing ions to pass through.
[0101] Positive electrode sheet
[0102] The positive electrode sheet includes a positive current collector and a positive active material layer disposed on at least one surface of the positive current collector, the positive active material layer including a positive active material.
[0103] As a non-limiting example, the positive current collector has two surfaces opposite each other in its own thickness direction, and the positive active material layer is disposed on either or both of the two opposite surfaces of the positive current collector.
[0104] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymeric material substrate and a metal layer formed on at least one surface of the polymeric material substrate. The composite current collector can be obtained by forming a metal material on a polymeric material substrate. Non-limiting examples of the metal material in the positive electrode current collector may include one or more of aluminum, aluminum alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys. Non-limiting examples of the polymeric material substrate in the positive electrode current collector may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).
[0105] In some embodiments, the positive electrode active material may be a known positive electrode active material for batteries. As a non-limiting example, the positive electrode active material may include one or more of the following materials: lithium-containing phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds. However, this application is not limited to these materials, and other conventional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides include, but are not limited to, one or more of lithium cobalt oxides (such as LiCoO2), lithium nickel oxides, lithium manganese oxides, lithium nickel cobalt oxides, lithium manganese cobalt oxides, lithium nickel manganese oxides, lithium nickel cobalt manganese oxides, lithium nickel cobalt aluminum oxides, and their modified compounds. Non-limiting examples of lithium-containing phosphates with an olivine structure include, but are not limited to, one or more of lithium iron phosphate, lithium iron phosphate and carbon composites, lithium manganese phosphate, lithium manganese phosphate and carbon composites, lithium iron manganese phosphate, and lithium manganese iron phosphate and carbon composites. Non-limiting examples of lithium cobalt oxides may include LiCoO2; non-limiting examples of lithium nickel oxides may include LiNiO2; non-limiting examples of lithium manganese oxides may include LiMnO2, LiMn2O4, etc.; non-limiting examples of lithium nickel cobalt manganese oxides may include LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also known as NCM) 333 LiNi 0.5 Co 0.2 Mn 0.3 O2 (also known as NCM) 523 LiNi 0.5 Co 0.25 Mn 0.25 O2 (also known as NCM) 211 LiNi 0.6 Co 0.2 Mn0.2 O2 (also known as NCM) 622 LiNi 0.8 Co 0.1 Mn 0.1 O2 (also known as NCM) 811 Examples of lithium nickel cobalt aluminum oxides include LiNi, etc. 0.8 Co 0.15 Al 0.05 O2.
[0106] Understandably, lithium (Li) is intercalated and deintercalated during the charging and discharging process of a battery, and the Li content in the positive electrode varies depending on the state of discharge. Unless otherwise specified, the Li content in the examples of positive electrode materials listed in this application refers to the initial state of the material. When a positive electrode material is applied to a positive electrode in a battery system, the Li content in the positive electrode material typically changes after charge-discharge cycles. The Li content can be measured using molar content, but is not limited to this. Regarding "Li content refers to the initial state of the material," the initial state of the material refers to its state before being added to the positive electrode slurry. It is understood that new materials obtained by appropriately modifying the listed positive electrode materials are also within the scope of positive electrode materials. The aforementioned appropriate modification refers to acceptable modification methods for the positive electrode material; non-limiting examples include coating modification.
[0107] In the examples of cathode materials in this application, the oxygen (O) content is only a theoretical value. Lattice oxygen release will cause changes in the molar content of oxygen, and the actual O content will fluctuate. The O content can be measured in molar content, but is not limited to this.
[0108] In some embodiments, the positive electrode active material may also include at least one of the following materials: sodium transition metal oxides, polyanionic compounds, and Prussian blue compounds. However, this application is not limited to these materials, and other conventionally known materials that can be used as positive electrode active materials for sodium-ion batteries may also be used.
[0109] As an optional technical solution in this application, the transition metal in the sodium transition metal oxide may include one or more of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce. A non-limiting example of a sodium transition metal oxide is Na. x MO2, where M can include one or more of Ti, V, Mn, Co, Ni, Fe, Cr and Cu, and 0 < x ≤ 1.
[0110] As an optional technical solution in this application, the polyanionic compound can be a compound containing sodium ions, transition metal ions, or a tetrahedral (YO4) structure. n-A class of compounds with anionic units. Transition metals may include one or more of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce; Y may be one or more of P, S, and Si; n represents (YO4). n- The price state.
[0111] Polyanionic compounds can also contain sodium ions, transition metal ions, or tetrahedral (YO4) ions. n- A class of compounds consisting of anionic units and halide anions. Transition metals may include one or more of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce; Y may be one or more of P, S, and Si, and n represents (YO4). n- The valence state; halogens can be one or more of F, Cl and Br.
[0112] Polyanionic compounds can also be sodium-containing tetrahedral (YO4) compounds. n- Anionic unit, polyhedral unit (ZO) y ) m+ And a class of compounds with optional halide anions. Y can be one or more of P, S, and Si, and n represents (YO4). n- The valence state; Z represents a transition metal, which can include one or more of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce, and m represents (ZO). y ) m+ The valence state; halogens can be one or more of F, Cl and Br.
[0113] Polyanionic compounds can include NaFePO4, Na3V2(PO4)3 (sodium vanadium phosphate, abbreviated as NVP), Na4Fe3(PO4)2(P2O7), NaM'PO4F and Na3(VO y )2(PO4)2F 3-2y One or more of (0≤y≤1). Among them, M' in NaM'PO4F can include one or more of V, Fe, Mn and Ni.
[0114] Prussian blue compounds can contain sodium ions, transition metal ions, and cyanide ions (CN). - A class of compounds containing Prussian blue. Transition metals may include one or more of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce. A non-limiting example of Prussian blue compounds is Na. a Me b Me' c(CN)6, wherein Me and Me' can each independently be one or more of Ni, Cu, Fe, Mn, Co and Zn, 0 < a ≤ 2, 0 < b < 1, 0 < c < 1.
[0115] In some embodiments, the positive electrode active material layer may optionally include a binder. As a non-limiting example, the binder may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resins.
[0116] In some embodiments, the positive electrode active material layer may optionally include a conductive agent. As a non-limiting example, the conductive agent may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0117] In some embodiments, the positive electrode sheet can be prepared by dispersing the components used to prepare the positive electrode sheet, such as the positive active material, conductive agent, binder, and any other components, in a solvent to form a positive electrode slurry; coating the positive electrode slurry onto at least one surface of the positive electrode current collector, and obtaining the positive electrode sheet after drying, cold pressing, and other processes. The solvent can be selected from, but is not limited to, any of the solvents described in the foregoing embodiments, such as N-methylpyrrolidone (NMP). The surface of the positive electrode current collector coated with the positive electrode slurry can be a single surface of the positive electrode current collector or both surfaces of the positive electrode current collector. The solid content of the positive electrode slurry can be 40wt%~80wt%. The viscosity of the positive electrode slurry at room temperature can be adjusted to 5000~25000 mPa·s. When coating the positive electrode slurry, the coating areal density (dry weight, minus solvent) can be 15~35 mg / cm². 2 The compaction density of the positive electrode sheet can be 3.0~3.6 g / cm³. 3 The concentration can be selected as 3.3~3.5 g / cm³. 3 .
[0118] Negative electrode sheet
[0119] The negative electrode sheet includes the negative current collector of the first or second aspect of this application, and a negative active material layer disposed on at least one surface of the negative current collector, the negative active material layer including a negative active material.
[0120] As a non-limiting example, the negative electrode current collector has two surfaces opposite each other in its own thickness direction, and the negative electrode active material layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.
[0121] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymeric material substrate and a metal layer formed on at least one surface of the polymeric material substrate. The composite current collector can be obtained by forming a metal material on the polymeric material substrate. Non-limiting examples of the metal material in the negative electrode current collector may include one or more of copper, copper alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys. Non-limiting examples of the polymeric material substrate in the negative electrode current collector may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).
[0122] In some embodiments, the negative electrode active material may be a negative electrode active material known in the art for use in batteries. As a non-limiting example, the negative electrode active material may include one or more of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate, etc. Silicon-based materials may include one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. Tin-based materials may include one or more of elemental tin, tin oxide compounds, and tin alloys. However, this application is not limited to these materials, and other conventional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0123] In some embodiments, the negative electrode active material layer may optionally include a binder. The binder may include one or more of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0124] In some embodiments, the negative electrode active material layer may optionally include a conductive agent. The conductive agent may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0125] In some embodiments, the negative electrode active material layer may also optionally include other additives, such as thickeners (e.g., sodium carboxymethyl cellulose (CMC-Na)).
[0126] In some embodiments, the negative electrode sheet can be prepared by dispersing the components used to prepare the negative electrode sheet, such as the negative electrode active material, conductive agent, binder, and any other components, in a solvent (a non-limiting example of a solvent is deionized water) to form a negative electrode slurry; coating the negative electrode slurry onto at least one surface of a negative electrode current collector, and then obtaining the negative electrode sheet after drying, cold pressing, and other processes. The surface of the negative electrode current collector coated with the negative electrode slurry can be a single surface of the negative electrode current collector or both surfaces of the negative electrode current collector. The solid content of the negative electrode slurry can be 40wt%~60wt%. The viscosity of the negative electrode slurry at room temperature can be adjusted to 2000~10000 mPa·s. When coating the negative electrode slurry, the coating unit areal density (dry weight, deducting solvent) can be 75~220 g / m². 2 The compaction density of the negative electrode sheet can be 1.0 g / cm³. 3 ~1.8g / cm 3 .
[0127] electrolytes
[0128] Electrolytes function to conduct ions between the positive and negative electrode plates. This application does not impose any particular restrictions on the type of electrolyte; it can be selected according to requirements. For example, the electrolyte can be liquid, gel, or completely solid.
[0129] In some embodiments, the electrolyte is an electrolyte solution. The electrolyte solution includes an electrolyte salt and a solvent.
[0130] In some embodiments, the electrolyte salt may include one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorophosphate (LiPO2F2), lithium difluorooxalate borate (LiDFOB), lithium dioxalate borate (LiBOB), lithium difluorodioxalate phosphate (LiDFOP), and lithium tetrafluorooxalate phosphate (LiTFOP).
[0131] In some embodiments, the solvent may include one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butene carbonate, fluoroethylene carbonate (FEC), methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone.
[0132] In some embodiments, the electrolyte may optionally include additives. For example, additives may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain battery performance, such as additives that improve battery overcharge performance, additives that improve battery high-temperature or low-temperature performance, etc.
[0133] In some embodiments, the additives in the electrolyte may include, but are not limited to, one or more of fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), trifluoromethyl ethylene carbonate (TFPC), etc.
[0134] Separating membrane
[0135] In some embodiments, the secondary battery also includes a separator. This application does not impose any particular limitation on the type of separator; any known porous separator with good chemical and mechanical stability can be selected.
[0136] In some embodiments, the material of the separator may include one or more of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator may be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer may be the same or different, without particular limitation.
[0137] In some embodiments, the thickness of the isolation membrane is 6~40μm, optionally 12~20μm.
[0138] In some embodiments, the positive electrode, negative electrode, and separator can be fabricated into an electrode assembly using a winding process or a stacking process.
[0139] In some embodiments, the secondary battery may include an outer packaging. This outer packaging may be used to encapsulate the electrode assembly and electrolyte described above.
[0140] In some embodiments, the outer packaging of the secondary battery can be a rigid shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery can also be a soft pack, such as a pouch-type soft pack. The material of the soft pack can be plastic; further, non-limiting examples of plastic may include one or more of polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0141] A secondary battery includes at least one battery cell. A secondary battery may include one or more battery cells.
[0142] In this application, unless otherwise specified, "cell battery" refers to the basic unit capable of converting chemical energy into electrical energy, and generally includes at least a positive electrode, a negative electrode, and an electrolyte. During the charging and discharging process of the battery, active ions move back and forth between the positive and negative electrode plates, inserting and extracting. The electrolyte acts as a conductor for the active ions between the positive and negative electrode plates.
[0143] This application does not impose any particular limitation on the shape of the battery cell; it can be cylindrical, square, or any other arbitrary shape. For example, Figure 2 The example shown is a square-structured battery cell 5.
[0144] In some of these embodiments, reference is made to Figure 3 The outer packaging may include a housing 51 and a cover 53. The housing 51 may include a base plate and side plates connected to the base plate, the base plate and side plates forming a receiving cavity. The housing 51 has an opening communicating with the receiving cavity, and the cover 53 can be placed over the opening to close the receiving cavity. The positive electrode, negative electrode, and separator may be formed into an electrode assembly 52 by a winding process or a stacking process. The electrode assembly 52 is encapsulated within the receiving cavity. Electrolyte is immersed in the electrode assembly 52. The number of electrode assemblies 52 contained in the battery cell 5 may be one or more, which can be selected by those skilled in the art according to actual needs.
[0145] The secondary battery can be either battery device 4 or battery pack 1.
[0146] The battery device includes at least one battery cell. The number of battery cells in the battery device can be one or more, and those skilled in the art can select an appropriate number according to the application and capacity of the battery device.
[0147] Figure 4 This is battery device 4, used as an example. (See reference...) Figure 4 In the battery assembly 4, multiple battery cells 5 can be arranged sequentially along the length of the battery assembly 4. Of course, they can also be arranged in any other manner. Furthermore, the multiple battery cells 5 can be fixed in place using fasteners.
[0148] Optionally, the battery device 4 may also include a housing with a receiving space in which multiple battery cells 5 are received.
[0149] In some embodiments, the battery devices described above can also be assembled into a battery pack, and the number of battery devices contained in the battery pack can be one or more. Those skilled in the art can select an appropriate number according to the application and capacity of the battery pack.
[0150] Figure 5 and Figure 6 This is battery pack 1 as an example. (See reference...) Figure 5and Figure 6 The battery pack 1 may include a battery box and multiple battery devices 4 disposed within the battery box. The battery box includes an upper body 2 and a lower body 3, with the upper body 2 covering the lower body 3 to form a closed space for accommodating the battery devices 4. The multiple battery devices 4 can be arranged in any manner within the battery box.
[0151] Thirdly, this application also provides an electrical device, which includes the secondary battery provided in this application. The secondary battery can be used as the power source of the electrical device or as the energy storage unit of the electrical device. The electrical device may include, but is not limited to, mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc. Among them, mobile devices may be, for example, mobile phones, laptops, etc.; electric vehicles may be, for example, pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc., but are not limited to.
[0152] As an electrical device, a rechargeable battery can be selected based on its usage requirements.
[0153] Figure 7 Here is an example of an electrical device 6. This electrical device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. To meet the high power and high energy density requirements of the secondary battery for this electrical device, a battery pack or battery device can be used.
[0154] Another example device could be a mobile phone, tablet, or laptop. These devices typically require a slim and lightweight design and can use a rechargeable battery as their power source.
[0155] Example
[0156] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where the technology or conditions are not specified in the embodiments, they are performed according to the technology or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.
[0157] Example 1
[0158] (1) Select an aluminum foil with a length of 300 mm, a width of 200 mm, and a thickness of 6 μm, and perform degreasing, acid-base corrosion and alkaline-acid corrosion treatment to obtain a base layer.
[0159] (2) At 27°C, the substrate layer is immersed in the zinc immersion solution for 30 seconds and then removed for the first zinc immersion treatment. The first zinc immersion layer is removed with dilute nitric acid solution for 30 seconds. The dezincified substrate layer is then immersed in the zinc immersion solution for 15 seconds and removed for the second zinc immersion treatment, forming zinc layers on opposite sides of the substrate layer. The zinc immersion solution has the following formula: zinc oxide concentration of 25 g / L, sodium hydroxide concentration of 125 g / L, potassium sodium tartrate concentration of 50 g / L, ferric chloride concentration of 2 g / L, and sodium nitrate concentration of 1 g / L. The thickness of the zinc layer on one side of the substrate layer is 20 nm.
[0160] (3) The product obtained in step (2) is used to prepare a nickel-iron layer on the zinc layer by electroplating. The electroplating solution consists of: 200 g / L nickel sulfate, 40 g / L nickel chloride, 50 g / L ferrous sulfate, 40 g / L boric acid, 30 g / L citric acid as a complexing agent, 10 g / L hydroquinone as a stabilizer, 3 g / L saccharin as the main brightener, 0.5 g / L 1,4-butynediol as a secondary brightener, and 0.1 g / L sodium dodecyl sulfate as a wetting agent.
[0161] Electroplating parameters are: current density 10A / dm 2 Temperature 50℃, pH 2.5, coating thickness 1μm.
[0162] (4) The product obtained in step (3) is immersed in a passivation solution at 60°C for 1 min to form an antioxidant layer containing chromium oxide; the formula of the passivation solution is as follows: chromium trioxide 5 g / L, sulfuric acid 30 g / L, nano silica 1 g / L, fluoroboric acid 10 g / L. The thickness of the antioxidant layer is 20 nm.
[0163] Example 2
[0164] The preparation process is similar to that in Example 1, the main difference being that the temperature in step (3) is 45°C and the current density is 5A / dm³. 2 This results in an average grain size of 13 nm for the metal grains in the nickel-iron layer.
[0165] Example 3
[0166] The preparation process is similar to that of Example 1, the main difference being that the temperature in step (3) is 65°C and the current density is 30A / dm³. 2 This results in an average grain size of 16 nm for the metal grains in the nickel-iron layer.
[0167] Example 4
[0168] The preparation process is similar to that of Example 1, the main difference being that the temperature in step (3) is 65°C and the current density is 30A / dm³. 2 Without adding 1,4-butynediol, the average grain size of the metal grains in the nickel-iron layer is 23 nm.
[0169] Example 5
[0170] Similar to the preparation process in Example 1, the main difference is that in step (2), the formula of the zinc immersion solution is adjusted to the conventional electroplating zinc immersion solution formula: zinc oxide 100g / L, sodium hydroxide 500g / L, ferric chloride 1g / L, potassium sodium tartrate 10g / L, to prepare a zinc layer of the same thickness.
[0171] Example 6
[0172] Similar to the preparation process in Example 1, the main difference is that in step (2), the zinc immersion solution formula is replaced with: copper sulfate 25g / L, sodium hydroxide 15g / L, formaldehyde 15mL / L, potassium sodium tartrate 45g / L, sodium EDTA salt 15g / L, so that the zinc layer is replaced with a copper layer of equal thickness.
[0173] Example 7
[0174] The preparation process is similar to that of Example 1, except that step (2) is omitted and no zinc layer is set.
[0175] Comparative Example 1
[0176] Similar to the preparation process of Example 1, the main difference is that in step (3), a chemical nickel layer of the same thickness is prepared by chemical nickel process, and the composition of the plating solution is: 30g nickel sulfate, 10g / L ferrous sulfate, 35g / L sodium hypophosphite, 70g / L sodium citrate, 15g / L lactic acid, 15g / L sodium acetate, and 1mg / L thiourea.
[0177] The electroless plating parameters were: temperature 90℃, pH 9.5, stirring speed 200 rpm, and coating thickness 1μm.
[0178] Test section
[0179] (1) Bonding strength test
[0180] Cut the sample into 30mm wide pieces, apply 3M double-sided tape to the steel plate, attach the sample flatly onto the double-sided tape, and then attach the sample flatly onto the special yellow tape (24mm wide). Use a tensile testing machine at 50mm / min and 180° peel to observe the adhesion strength; the adhesion strength = the sum of the adhesion strengths of 10 test samples / 10.
[0181] (2) Elongation test
[0182] According to GB / T 5230-1995 "Electrolytic Copper Foil", tensile specimens were cut into length L0 values of 200 mm and widths of 15 mm. The specimens were weighed on a balance, and the mass was recorded as m. Tensile properties were tested using a universal testing machine at 25℃, with a tensile rate set to 50 mm / min. The cross-sectional area S0 of the tensile specimen is then calculated as S0 = m / (ρ × L0), where ρ is 8.96 g / cm³. 3 The unit of m is grams, and the unit of L0 is centimeters. The specimen is continuously loaded until it breaks. The maximum load F is read from the force measuring plate or the tensile curve, and the tensile strength σb is calculated according to Formula I: σb = F / S0 (Formula I). The distance between the two lines after the specimen breaks is L1, which can be measured on the specimen or read from the tensile curve. L1 can be measured using the linear method or the displacement method, and the (breakage) elongation δ is calculated according to Formula II: δ = (L1 - L0) / L0 (Formula II).
[0183] The performance tests of the negative electrode current collectors obtained in Examples 1-7 and Comparative Example 1 are shown in Table 1 below.
[0184] Table 1
[0185]
[0186] Table 1 shows that, compared with Comparative Example 1, Examples 1-7 can be compared with electroless nickel plating. The present application uses electroplating nickel to prepare the metal layer, which can form metal grains in the metal layer and make the metal layer have better ductility.
[0187] A comparison of Examples 1-4 with Example 7 shows that, compared with not setting a transition layer, setting a zinc transition layer can effectively improve the adhesion between the substrate layer and the metal layer; a comparison of Examples 1-4 with Example 6 shows that, compared with copper, zinc has a better adhesion effect; a comparison of Examples 1-4 with Example 5 shows that, compared with conventional zinc immersion solution formulations, the zinc immersion solution formulation specially controlled in this application is conducive to further improving the adhesion between the substrate layer and the metal layer.
[0188] The description of the various embodiments above tends to emphasize the differences between the various embodiments. The similarities or similarities between them can be referred to, and for the sake of brevity, they will not be repeated here.
[0189] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.
Claims
1. A secondary battery, characterized in that, The device includes a negative electrode sheet, which includes a negative current collector. The negative current collector includes a substrate layer and a metal layer disposed on at least one side of the substrate layer. The substrate layer is made of aluminum and / or magnesium, and the metal layer contains metal grains.
2. The secondary battery according to claim 1, characterized in that, The average grain size of the metal grains is 10 nm to 100 nm.
3. The secondary battery according to claim 1 or 2, characterized in that, The porosity of the metal layer is less than or equal to 2 particles / dm. 2 .
4. The secondary battery according to any one of claims 1 to 3, characterized in that, The elongation of a single metal layer is greater than or equal to 1%.
5. The secondary battery according to any one of claims 1 to 4, characterized in that, The negative electrode current collector also includes a transition layer disposed between the substrate layer and the metal layer, the transition layer comprising zinc.
6. A negative electrode current collector, characterized in that, The negative electrode current collector includes a substrate layer and a metal layer disposed on at least one side of the substrate layer, wherein the substrate layer is made of aluminum and / or magnesium, and the metal layer contains metal grains.
7. The negative electrode current collector according to claim 6, characterized in that, The negative electrode current collector in the secondary battery according to any one of claims 2 to 5.
8. A method for preparing a negative electrode current collector, characterized in that, include: A metal layer is prepared on at least one side of a substrate layer by an electroplating process, wherein the substrate layer is made of aluminum and / or magnesium, and the metal layer comprises metal grains.
9. The preparation method according to claim 8, characterized in that, Before preparing the metal layer, the process further includes: preparing a zinc-containing transition layer on at least one side of the substrate layer by a chemical zinc immersion process.
10. The preparation method according to claim 9, characterized in that, The zinc immersion solution in the chemical zinc immersion process comprises zinc oxide, sodium hydroxide, potassium sodium tartrate, ferric chloride, and sodium nitrate. In the zinc immersion solution, the concentration of zinc oxide is 20 g / L to 30 g / L, the concentration of sodium hydroxide is 110 g / L to 130 g / L, the concentration of potassium sodium tartrate is 45 g / L to 55 g / L, the concentration of ferric chloride is 1 g / L to 2 g / L, and the concentration of sodium nitrate is 1 g / L to 2 g / L.
11. An electrical appliance, characterized in that, Includes the secondary battery as described in any one of claims 1 to 5.